Women self-help groups and intra-household decision-making in agriculture - Subash Surendran Padmaja; Aditya Korekallu Srinivasa; Pooja Trivedi; Kondapi Srinivas (Annals of Public and Cooperative Economics, 2023)
This study examines the effect of women-centric agricultural self-help groups (SHGs) on intra-household decision-making in agriculture. Using data collected from an intra-household survey of 815 households, we analyze the effect of women's membership in different types of SHGs on 14 decisions related to farms and households. Specifically, we investigate the discord in decision-making, which is the difference in the perceived decision-making roles of spouses within a household. Our results show that women's participation in SHGs has increased their role in decision-making by 8–13%. However, the effects vary according to the type of intervention and the decision. We found fewer discords in intra-household decision-making in seed SHGs than in micro-finance SHGs. In conclusion, our study suggests that women's engagement in agriculture-based SHG interventions can encourage joint decision-making, but the magnitude of this effect depends on the type of SHG. Development agencies can use this information to design interventions targeted at empowering women through the improvement of the agricultural value chain.
Keywords: 330; intra-household discord; self-help groups (SHGs); women empowerment; farm households